Elements of rhythm and their connotations in the complete poetry collection of the poet Sayyed Haider Al-Hilli (The elegies of the Ahlol bayt, as an example) - Somayeh Hasan Alian; Amin Nazari Terizi; Hossein Nemah Alrekabi (دراسات فی اللغه العربیه و آدابها)
The impact of the incident of al-Taff, the martyrdom of Imam al-Hussein, peace be upon him, and his companions, and what happened to the Ahl Albait, from persecution, killing, and desecration, appeared in the literary arts, where we find the most wonderful elegies in the recording of these events and the great tragedy. And whose name emerges among the expressors of this great tragedy is the Shiite poet Sayyid Haider al-Hilli, where elegies constituted a basic section and a major theme of his poems, which need deep research in terms of style and context of poetry. So, this research aimed at a stylistic study of the rhythmic structure of Sayyid Haider al-Hilli's elegy, which was represented in the external and internal. rhythms. The results of the study indicate that Bahr al-Taweel, Compound Bahour and Complete Bahour are more frequent in elegies. And the poet was able to extract from one sea different musical melodies with the diversity of his emotions and feelings. The absolute rhyme formed a complete presence in the elegies, as the poet resorted to employing this type of rhyme for his desire to communicate his voice to the recipient with the greatest degree of clarity. The method of repetition in the elegies was consistent with the psychological state that the poet is going through, as well as the intended meaning that he seeks to present. The incomplete naturalization and derivational naturalization constitute a wide presence compared to the complete naturalization. This is attributed to the efforts made by the poet in bringing the concept and the desired meaning closer to the mind of the recipient in comparison to the complete naturalization that creates a kind of ambiguity in bringing the intended meaning closer.